Service Quality, Customer Value and Patient Satisfaction on Public Hospital in Bandung District, Indonesia - Suryadana, Liga (International Review of Management and Marketing, 2017)
The purpose of this research is to investigate the influence of service quality on customer value as well as on public hospital patient satisfaction. Population studies were conducted in government hospitals. Data analysis used structural equation modeling Partial Least Square (SEM-PLS). Sample in this research are 158 patients from government hospitals in the district Bandug, Indonesia. The results showed a significant influence on service quality on customer value and patient satisfaction. Furthermore, the results also showed that gender plays a role as moderating variable between customer value and patient satisfaction. This indicates that the services provided by public hospitals can improve customer value implications on patient satisfaction. Keywords: service quality, customer value, patient satisfaction, public hospital. JEL Classifications: M31, M38, I13